Relationship between Self-Control and Attitudes Towards Premarital Sexual Inisiation of Adolescence - Nada Annisah; Mudjiran Mudjiran; Z Mawardi Effendi (Journal of Educational and Learning Studies, 2020)
Adolescents are at risk and need serious attention, especially in sexuality in the development of adolescent life. Premarital sexual in Indonesia from time to time is very worrying. Nowadays teens consider premarital sexual as a normal and normal thing to do. Adolescent attitudes affect the behavior carried out.This study reveals the relationship of self-control with attitudes toward premarital sexual initiation of adolescence. This study uses the correlational method and data collected from a sample of 277 students, which were found using proportional random sampling techniques. Data were collected using a self-control scale (23 valid items, = 0.876), and a scale of adolescent attitudes about pre-wedding sexual behavior (25 valid items = 0.913). Data were analyzed using descriptive statistical methods, because to describe the object studied through the sample as it is. The results show that there is a negative and significant relationship between self-control and attitudes towards premarital sexual initiation of adolescence. It can be concluded that the higher the self control of students eating the lower the attitude of students towards premarital sexual initiation of adolescence.